2013
DOI: 10.1038/mt.2013.90
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of TAB1/p38α Interaction Using a Cell-permeable Peptide Limits Myocardial Ischemia/Reperfusion Injury

Abstract: Targeting the adaptor protein (transforming growth factor-β (TGF-β)-activated protein kinase 1 (TAK1)-binding protein 1) (TAB1)-mediated non-canonical activation of p38α to limit ischemia/reperfusion (I/R) injury after an acute myocardial infarction seems to be attractive since TAB1/p38α interaction occurs specifically in very limited circumstances and possesses unique structural basis. However, so far no TAB1/p38α interaction inhibitor has been reported due to the limited knowledge about the interfaces. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…TGF-β1 expression activity in cardiac muscle tissues of myocardial infarction rats was demonstrated to be markedly enhanced (26). Corresponding MAP3K7, p38 MAPK, and p-p38 MAPK protein activity were also clearly enhanced (26). The possible underlying mechanism involves TGF-β1 activating MAP3K7, thus causing p38 MAPK to be phosphorylated into p-p38 MAPK and enhancing inflammatory factor expression levels in rats, finally resulting in cardiac hypertrophy, interstitial fibrosis, serious cardiac insufficiency, myocardial apoptosis or mortality (25).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…TGF-β1 expression activity in cardiac muscle tissues of myocardial infarction rats was demonstrated to be markedly enhanced (26). Corresponding MAP3K7, p38 MAPK, and p-p38 MAPK protein activity were also clearly enhanced (26). The possible underlying mechanism involves TGF-β1 activating MAP3K7, thus causing p38 MAPK to be phosphorylated into p-p38 MAPK and enhancing inflammatory factor expression levels in rats, finally resulting in cardiac hypertrophy, interstitial fibrosis, serious cardiac insufficiency, myocardial apoptosis or mortality (25).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, TGF-β1 is involved in stimulating tissue fibrosis, causing increases in fibrocytes, MMPs, collagen deposition and fiber binding proteins, and results in ventricular remodeling (23). TGF-β1 expression activity in cardiac muscle tissues of myocardial infarction rats was demonstrated to be markedly enhanced (26). Corresponding MAP3K7, p38 MAPK, and p-p38 MAPK protein activity were also clearly enhanced (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mechanisms by which GPCR-stimulated TAB1-induced p38 MAPK signaling controls various inflammatory responses including induction of cytokine production and endothelial barrier disruption remains poorly understood and warrants further exploration. Finally, in vivo studies have documented the relevance of TAB1-p38␣ activation in various disease settings including myocardial ischemia (13,16,44), indicating that TAB1-dependent p38 activation will be likely important for endothelial dysfunction in vivo. A recent paper further showed that disruption of TAB1-p38␣ interaction in vivo reduced myocardial ischemic injury (14), suggesting that the development of small molecules targeting the TAB1-p38␣ interface may provide a specific therapeutic intervention with limited side effects, not otherwise achievable with global p38 inhibition.…”
Section: Non-canonical Activation Of P38 By Gpcrsmentioning
confidence: 99%
“…This includes local application of the peptides e.g. by direct injection into the brain leading to reduced cell damage in a stroke model [54] or decreased myocardial I/R injury [55,10] targeting two different proteins (JNK1, BH4). Another example is the protein kinase C delta inhibiting peptide Tat-deltaV-1injected into the internal carotid artery, which improved pathology after cerebral reperfusion injury [56,57].…”
Section: In Vivo Testing Of Cell Permeable Peptidesmentioning
confidence: 99%